Haptoglobin Genotype Affects Inflammation after Aneurysmal Subarachnoid Hemorrhage - Gusdon, Aaron M.; Savarraj, Jude; Zhu, Liang; Pandit, Peeyush K. Thankamani; Doré, Sylvain; McBride, Devin W.; Choi, HuiMahn A.; Blackburn, Spiros L. (Current Neurovascular Research, 2020)
Background: Haptoglobin (Hp) binds to and facilitates clearance of heme. Compared with HP 1-1 and 1-2 genotypes, HP 2-2 has a weaker binding affinity and has been linked with increased inflammation and vasospasm after aneurysmal subarachnoid hemorrhage (SAH). Objective: This study aims to assess levels of inflammatory cytokines in the context of different HP genotypes. Methods: Patients were enrolled among those presenting with spontaneous aneurysmal SAH. Blood was drawn at four time points; <24 hours (T1), 24-48 hours (T2), 3-5 days (T3), and 6-8 days (T4). Blood was analyzed for levels of 41 cytokines at each time point, as well as for HP genotypes. These data were analyzed using mixed-effect models to assess the association between HP genotypes and cytokine levels. The modified Rankin Scale (mRS) score was obtained at discharge, 3 months, and 6 months. Results: Fifty-seven patients were enrolled. Compared with HP 1-1 and 1-2, subjects encoding HP 2-2 had elevated levels of the following cytokines at all time points: FLT3L, IFNγ, IL-17A, TGFα, and VEGF-A. Elevations were also seen at some time points for IL-8, CSF2, FGF2, IL-7, IL-12p70, and TNFα. This study was not powered to detect differences in the functional outcome; however, there were no significant differences in dichotomized mRS scores between patients with HP 1-1/1-2 or HP 2-2. Conclusion: Our findings indicate that HP 2-2 genotype leads to increased proinflammatory cytokine levels compared with HP 1-1/1-2 genotypes. These data may provide guidance for further studies seeking to identify testable markers for functional prognosis or targets for treatment.
Keywords: subarachnoid hemorrhage